Advantages and disadvantages with outdoor hutches as housing system for calves and their future effect on the replacement heifer - Lundell, Anna (SLU/Dept. of Animal Nutrition and Management (until 231231), 2015)
This study has investigated how outdoor hutches for housing dairy heifer calves will have negative and positive effects on calf development. Many studies have shown that an optimal rearing of the young calf is of great importance to up bring a profitable dairy cow. The dairy calf and growing heifer is subject for a great scientific interest. Within its first days the young animal will be separated from the dam. Then during a few months it will be kept individually or collectively with other calves and drink milk from buckets or suckle from artificial teats. Housing calves in hutches during this period can have many advantages. Later she will be impregnated and carry her own calf. When her pregnancy comes to its end she will in only a day go through her first calving and get milked or suckled her first produced milk. Thereafter she will enter the most important income bringing part of the dairy farm. To get the optimal prerequisites for the lactation period, the rearing is of great importance. A healthy calf will have a higher average daily gain, and grow to a higher weight and stature. The heifer is more likely to have a higher milk yield at first and future lactations if she was not ill as a calf. Many dairy producers in Sweden keep calves in pens inside a stable. Housing outside in hutches, where ventilation and humidity is natural, can be a healthier alternative for calves. Some disadvantages from housing calves outside in hutches do exist and is also discussed.